Introduction: Development of tense and aspect systems - Gvozdanović, Jadranka (Journal of historical linguistics, 2020)
Abstract This introduction discusses the construal of temporal categories, their connection with spatial categories and general principles of the patterning of time in language. Transfers between categories and up language hierarchies are frequent types of change. It is shown how aspect may either lose or increase some of its functional load, and how tenses may develop from aspects, or extend into modal domains. General tendencies (such as developments from spatial to temporal categories) and systemic constraints are discussed in relation to the papers in this volume with additional Indo-European examples.
Gesehen am 21.03.2025